2015
DOI: 10.3354/ab00616
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of freshwater invertebrate sampling methods in a shallow aridland river (Rio Grande, New Mexico)

Abstract: Aridland rivers can present several logistical challenges for invertebrate sampling due to shifting substrate and low invertebrate densities. We compared 4 sampling methods for collecting both meiofauna and macroinvertebrates in an aridland river (Rio Grande, New Mexico): a water column sampling method, an epibenthic core, a throwtrap, and a stovepipe sampling method. The objective of this study was to find the most efficient combination of sampling methods with which to collect the entire assemblage. Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The increase in predators in the absence of wastewater was also found by other studies relating declines in predators as a result of increased nutrients and anthropogenic disturbances (Fu et al 2016 ; Zhang et al 2019 ). Corixidae, in particular, have been commonly observed in other studies in Rio Grande habitats (Bain et al 2011, Burdett et al 2015 ), which we found were generally lower in nutrients than wastewater fed sites.…”
Section: Discussionsupporting
confidence: 76%
“…The increase in predators in the absence of wastewater was also found by other studies relating declines in predators as a result of increased nutrients and anthropogenic disturbances (Fu et al 2016 ; Zhang et al 2019 ). Corixidae, in particular, have been commonly observed in other studies in Rio Grande habitats (Bain et al 2011, Burdett et al 2015 ), which we found were generally lower in nutrients than wastewater fed sites.…”
Section: Discussionsupporting
confidence: 76%
“…The percent Odonata, EOT and Predators also increased signi cantly within non-wastewater sites, likely due to their sensitivity to anthropogenic impacts (Kutcher and Bried 2014). The increase in Predators may also be explained by increased presense of macroinvertebrates such as corixidae within the Rio Grade water column (Burdett et al 2015). Since there were multiple sites ooed with river water and two sites at the river itself, this may have led to an increase in Predators sampled from these sites.…”
Section: Nutrientsmentioning
confidence: 99%
“…The effectiveness and efficiency of macroinvertebrate sampling protocols have been assessed for both regulatory and research purposes (Burdett et al, 2015; Buss et al, 2015; Ghani et al, 2016; Lenat, 1988; Stein et al, 2008), typically comparing individual sampling methods with each other (e.g., kicknet, Dnets, and serber samples), rather than combinations of different sampling methods (Burdett et al, 2015; Ghani et al, 2016; Stein et al, 2008; Tronstad and Hotaling, 2017; Tubić et al, 2017). Dnets and strainers were assessed for similarity between the sampling methods gauged by Sørensen similarity index for the purpose of water quality assessments (Stein et al, 2008).…”
Section: Stream Sampling Locations and Dates In Great Smoky Mountainsmentioning
confidence: 99%
“…Dnets and strainers were assessed for similarity between the sampling methods gauged by Sørensen similarity index for the purpose of water quality assessments (Stein et al, 2008). Serber nets were recommended for both regulatory and aquatic ecosystem productivity studies (Burdett et al, 2015), whereas kicknet sampling features prominently in aquatic method studies for the collection of samples with high abundance and richness (Everall et al, 2017; Ghani et al, 2016). A combination of standardized qualitative methods (two kicknet samples, three Dnet samples, one leaf pack sample, three aufwuchs samples, one sand sample, and visual collections) were compared with semiquantitative kicknet sampling by the North Carolina Division of Environmental Management (now the North Carolina Department of Environmental Quality) (Lenat, 1988).…”
Section: Stream Sampling Locations and Dates In Great Smoky Mountainsmentioning
confidence: 99%